2013
DOI: 10.1080/1068316x.2013.793331
|View full text |Cite
|
Sign up to set email alerts
|

Geographical profiling in a novel context: prioritising the search for New Zealand sex offfenders

Abstract: The present work examines the use and value of geographical offender profiling methodologies within a novel context, considering both theoretical and practical issues relating to their application.Two separate studies are presented. The first examined the effectiveness of a geographical profiling system (Dragnet) for a sample of 101 New Zealand sex offenders, comparing findings with those obtained for a U.K. serial rape sample. Search costs and search cost functions (relating proportions of the samples to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…When targets are more dispersed there are fewer crime opportunities within a given distance range, resulting in longer distances between activity nodes and crime and an extended decay curve. Accordingly, New Zealand burglary and sex offenders' home-crime distances are longer on average than those of offenders from other countries (Hammond 2014;Lundrigan et al 2010;Lundrigan and Czarnomski 2006;Scott 2012). Likewise, Townsley et al (2015) found a smaller association between distance to home and residential burglary location choice in Australia than in the UK and the Netherlands, reflecting differences in urban population density.…”
Section: Discussionmentioning
confidence: 99%
“…When targets are more dispersed there are fewer crime opportunities within a given distance range, resulting in longer distances between activity nodes and crime and an extended decay curve. Accordingly, New Zealand burglary and sex offenders' home-crime distances are longer on average than those of offenders from other countries (Hammond 2014;Lundrigan et al 2010;Lundrigan and Czarnomski 2006;Scott 2012). Likewise, Townsley et al (2015) found a smaller association between distance to home and residential burglary location choice in Australia than in the UK and the Netherlands, reflecting differences in urban population density.…”
Section: Discussionmentioning
confidence: 99%
“…That the activity spaces frequently spanned multiple urban areas is consistent with the few NZ studies of the distances between offenders' home addresses and their offenses, and of the mobility of New Zealanders in general. In NZ, the home-crime distances of sex offenders tend to be longer on average than overseas, with higher proportions of "commuter" offenders whose homes are outside the radius of their offenses [61][62][63][64]. Davidson's [65] study of Christchurch burglars' home-crime distances found more geographically constrained patterns but may not represent contemporary trends, given changes in societal travel patterns and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Derivado de ello, surge la perfilación geográfica (geographical offender profiling), enfocada en los patrones de movilidad geoespacial presentes en una serie de delitos vinculados entre sí, con el objeto de comprender los procesos cognitivos-adoptados por un sujeto-en lo relativo al ámbito espacio-temporal (temporalidad, trayectoria, distancia, frecuencia); esto permite inferir las características del sujeto, tras el análisis de los crímenes y, con ello, acotar el rango de posibles sospechosos (Hammond & Youngs, 2011;Knabe-Nicol & Alison, 2011;Snook et al, 2005). Además de su aplicabilidad y de la evidencia reportada en la investigación de homicidios (Avdija et al, 2021) se ha documentado su utilidad en delitos de agresión sexual (Hammond, 2014) e incendios (Ducat et al, 2015).…”
Section: La Evaluación Psicológica Reconstructiva (Epr)unclassified